Validation of soil test based fertilizer recommendations for targetted yield of direct sown paddy in north coastal zone of Andhra Pradesh - Rani, T. Usha; Sreelatha, T.; Ch, Ramalaxmi; Rao, V.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted at RARS, Anakapalle during 2008-2010 to find out the fertilizer requirement for targeted yields. The experiment had five treatments T1 : 100% rec. dose of fertilizers (control) T2,T3,T4 supply of fertilizer based on targeted yield of 5t, 6 t/ha, and 7 t/ha respectively and T5 supply of fertilizer based on 30% change on soil test value. The yield obtained in soil test based targeted yield (STTY) for 7 t/ha (5.24 t/ha) was significantly higher than the recommended dose of fertilizer. The yield response in kg/kg fertilizers was also the highest for this treatment. Again, applying fertilizers based on targeted yield of 7 t/ha recorded the highest while the recommended dose of fertilizers recorded the lowest uptake of nutrients. The available nutrient status in soil after harvesting of paddy was higher in the treatment of targetted yield of 7 t/ha.